Sistem Informasi Pembayaran Tagihan Layanan Internet Berbasis Website di PT Indonesia Comnets Plus - Faqih Fauzia Septiana; Teguh Khristianto (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Internet technology is currently developing rapidly, the need for internet in the community in the current era of the COVID-19 pandemic is increasing because studying and working can be done at home. By utilizing technology, processing customer bill payment data will be faster because of the ease of use. To support the implementation of this inseparable development of Information and Technology, a website-based internet bill payment system was created with the aim of making it easier for customers to make payments and check payment history and provide convenience for the field of collection in checking accounts receivable data so that they can be followed up in accordance with standard operating procedures. applicable. So that customers feel comfortable because they don't need to be constantly reminded regarding missed payments. The design of the internet service bill payment system is described by Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD). The design of the system prototype uses the PHP programming language and the PostgreSQL database. From this study, it was found that the website-based internet bill payment system was running well. In appearance, the website is responsive to many browsers. Meanwhile, in terms of functionality, the system can perform the functions of each feature.